The relationship between resilience, anxiety, and depression in Chinese collegiate athletes - Lyu, Chengjie; Ma, Rong; Hager, Ronald; Porter, Dave (Frontiers in Psychology, 2022)
Anxiety disorder is becoming increasingly prevalent across college campuses, particularly among collegiate athletes who face different stressors and challenges than their non-athlete peers. Anxiety and depression are well documented comorbidities. Furthermore, the number of Chinese college students and collegiate athletes suffering from anxiety and depression is increasing. Psychologists have recently begun to take a more prophylactic approach to defend against these disorders through resilience intervention. Resilience intervention focuses on developing greater capacity to cope when mental and emotional challenges arise. The purpose of this study was to analyze the relationship between resilience, depression, and anxiety in Chinese collegiate athletes. The study outcomes provide added evidence of the value of incorporating an effective resilience educational module for collegiate athletes to thrive when faced with any adversity. Research Design: The study employed a survey research design to explore the complex relationship between depression, anxiety, and resilience for collegiate student athletes. Data Analysis Strategy: Structural Equation Modeling (SEM) was employed to account for any measurement error between the observed items (responses on the instruments) and the latent variables (anxiety, depression, and resilience). More importantly, SEM examined whether the collected data support the theoretical model proposed in this research. Key Measures: levels of anxiety, depression, and resilience in current collegiate athletes in Guangdong Province, Peoples Republic of China